Peningkatan Kemampuan Menghitung Pecahan melalui Pembelajaran CTL di MI Negeri Peureulak - Fitri Auliyani; Asmaul Husna; Nur Arifah Tatsa; Yusaini . (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2020)
Learning mathematics in elementary school should use several learning strategies, thegoal is to facilitate the teaching and learning process. Based on the results ofpreliminary observations in four grade showed that students were not able to countthe same-denominated fractions and those with different denominations. The use ofthis contextual teaching and learning (CTL) strategy aims to improve the ability tocount students and to find out the activities carried out by students, especially infraction material in four grade of MIN Peureulak. This research is a classroom actionresearch (PTK), carried out in two cycles at IV/a class. The instrumens used to obtaindata in this study were tests and observations. Data were analyzed using thepercentage formula. The results showed that there was an increase in the level ofcompleteness of student learning outcomes slassically in cycle one totaling 42%. In thesecond cycle increased to 77%, and there was an increase in student learning activitiesis in cycle one totaling 73% and cycle two it increase to 87%. Based on the results ofthis it can be concluded that the application of contextual teaching and learning (CTL)strategies can improve student’s counting abilities and can improve learning activitiesespecially in fraction material in four grade of MIN Peureulak